Scoping review of happiness and well-being measurement: uses and implications for paediatric surgery in low- and middle-income contexts - Carrie Dolan; Jillian Harrison; Cate Pringle (BMJ Open)
Objective This study aims to map and compare existing methodologies for creating happiness and well-being indices and examine their application to paediatric surgical interventions in low- and middle-income countries (LMICs).Design A scoping review methodology was used based on the guidelines published by the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews.Data sources Literature was sourced from PubMed, ScienceDirect and Google Scholar, supplemented by references from relevant studies.Eligibility criteria Studies were selected based on relevance to LMIC settings, paediatric surgery and well-being or happiness outcomes. Inclusion criteria covered research on paediatric surgical interventions, well-being measures, happiness indices and studies on specific conditions impacting child well-being in LMICs. Exclusions applied to non-English studies, those with unclear methods, undefined well-being concepts, a focus on socioeconomic indices, surgical techniques over outcomes or those published before 2000. Eligible sources included research articles, review articles and technical reports.Data extraction and synthesis Two reviewers independently extracted data, including study characteristics, populations, methodologies and key findings. The data were organised in an Excel spreadsheet for clarity and accuracy. A total of 51 sources were initially identified, with 28 included in the final review.Results The review revealed a broad range of well-being measurement techniques, from national population-level indices to health-related quality-of-life measures. A key finding was the strong reciprocal relationship between subjective well-being and physical health: subjective well-being impacts health outcomes, while health outcomes influence subjective well-being. However, the lack of standardised methods for assessing well-being postsurgery, particularly in LMICs, leads to inconsistent and fragmented data that complicate resource allocation and comparisons between interventions.Conclusions This review highlights the importance of integrating comprehensive well-being measures, particularly subjective assessments, into paediatric surgical contexts within LMICs. Such integration is critical to enhance global health interventions and capture the broader impacts of surgical care on well-being and happiness.